Anorexia nervosa: aetiology, assessment, and treatment - Zipfel, Stephan; Giel, Katrin; Bulik, Cynthia M; Hay, Phillipa; Schmidt, Ulrike (The lancet. Psychiatry, 2015)
Anorexia nervosa is an important cause of physical and psychosocial morbidity. Recent years have brought advances in understanding of the underlying psychobiology that contributes to illness onset and maintenance. Genetic factors influence risk, psychosocial and interpersonal factors can trigger onset, and changes in neural networks can sustain the illness. Substantial advances in treatment, particularly for adolescent patients with anorexia nervosa, point to the benefits of specialised family-based interventions. Adults with anorexia nervosa too have a realistic chance of achieving recovery or at least substantial improvement, but no specific approach has shown clear superiority, suggesting a combination of re-nourishment and anorexia nervosa-specific psychotherapy is most effective. To successfully fight this enigmatic illness, we have to enhance understanding of the underlying biological and psychosocial mechanisms, improve strategies for prevention and early intervention, and better target our treatments through improved understanding of specific disease mechanisms.
Gesehen am 06.10.2020